Composition and diversity of helminth communities in eels anguilla anguilla in the river tiber: long-term changes and comparison with insular europe - Kennedy, CR; BERRILLI, FEDERICA; DI CAVE, DAVID; De Liberato, C; ORECCHIA, PAOLA (Cambridge University Press, 1998)
Most studies of helminth communities in the European eel Anguilla anguilla have been undertaken in the British Isles, and there are very few analyses of community composition and structure from continental Europe. To fill this gap and test the hypothesis that helminth communities in freshwater eels in the British Isles are not typical of those of continental Europe, helminth communities of eels in the River Tiber below Rome were analysed by season using data collected in 1980 and new data from 1996. The intestinal helminth communities in the Tiber eels were species poor and characterized by low diversity. Most eels harboured one or no parasite species and communities were heavily dominated by the acanthocephalan Acanthocephalus clavula. Intestinal helminth infracommunity richness and diversity did not differ between seasons within a year or between the same seasons in 1980 and 1996, although some changes in composition were apparent. Intestinal infracommunities from Tiber eels were very similar in characteristics to those analysed from the British Isles, and their temporal changes also showed close similarities to those reported from rivers in the UK. It seems likely therefore that conclusions derived from British studies can be applied to helminth communities of eels on the continent.